STRATEGI PEMBERDAYAAN MASYARAKAT NELAYAN PANCING TONDA (TROLL LINE) DI KECAMATAN LEIHITU - Yofita Anaktototy (PAPALELE: Jurnal Penelitian Sosial Ekonomi Perikanan dan Kelautan, 2017)
Community empowerment strategies for proper trolling fishing rod is (1)a strategy SO (strengths - opportunities) include optimization of tuna fishing, fishing capacity increase in the development of fishing fleets, catches produki marketing Optimization, Increasing access to reach the fishermen in the fishing area, (2) strategies WO (weaknesses - opportunities) covering Increased independence of fishermen in the fishing business investment, Increasing access to fishermen in developing policies to accommodate the fishing fleet, fishing capacity increase in handling fresh fish production according to market demand, (3) the strategy ST (strength - threats) include increased access to capital at the level of fishing, the increase in levels of savings culture fishermen fishing for business development, development of the fuel depot at the fishing settlement, (4) strategies WT (weaknesses - threats) include alternative pencahrian eye development, capacity building of fishermen in the underwriting business, the market price control policy intervention, program development subsidies for fisherman.